2010
DOI: 10.1177/0363546510370196
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Clinical Outcomes in Patients Undergoing Meniscectomy

Abstract: Knee meniscectomy is the most common procedure performed by orthopaedic surgeons. While it is generally believed that loss of meniscal tissue leads to osteoarthritis and poor knee function, many variables may significantly influence this outcome. Through literature search engines including PubMed and Ovid, 4 randomized controlled trials, 2 prospective cohorts, and 23 retrospective cohorts that fit the criteria for level I, II, and III level of evidence were included in this systematic review. For the level III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
171
0
13

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(187 citation statements)
references
References 58 publications
(156 reference statements)
3
171
0
13
Order By: Relevance
“…7,15 Many studies have confirmed the importance of the meniscus to the knee joint, and its loss is associated with instability and degeneration of the joint. 38 There are 2 main groups of patients with meniscus injuries who undergo arthroscopy: those with acute injuries and those with degenerative injuries. Acute lesions generally occur when an axial load is transmitted directly to the flexed knee associated with rotation.…”
mentioning
confidence: 99%
“…7,15 Many studies have confirmed the importance of the meniscus to the knee joint, and its loss is associated with instability and degeneration of the joint. 38 There are 2 main groups of patients with meniscus injuries who undergo arthroscopy: those with acute injuries and those with degenerative injuries. Acute lesions generally occur when an axial load is transmitted directly to the flexed knee associated with rotation.…”
mentioning
confidence: 99%
“…1,2 Radial tears in the avascular zone requires partial meniscectomy. 3 Total meniscectomy increases the risk of premature osteoarthritis, so partial meniscectomy has proven the better choice after meniscal lesions. 4,5 However, partial meniscectomy can also lead to degenerative radiological signs.…”
mentioning
confidence: 99%
“…The meniscus plays a pivotal role in load transfer and knee stabilisation during normal joint motion. Damage to the meniscus exposes articular surfaces to excessive peak stresses and predisposes them to cartilage degeneration and progressive osteoarthritis (2,3). In pursuit of a feasible clinical substitute for damaged meniscus, clinical evidence supports the use of fresh frozen allografts (4)(5)(6) or as an alternative, synthetic meniscus replacements such as the Collagen Meniscus Implant (Ivy Sports Medicine) (7)(8)(9) or Actifit® (a polyurethane meniscus implant; Orteq) (10).…”
Section: Introductionmentioning
confidence: 99%